PENGARUH REWARD AND PUNISHMENT, DAN BUDAYA KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada Kecamatan Mangaran, Panji, dan Situbondo) - Pranata, Joan; Arief, Mohammad Yahya; W, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2022)
Human resource management is a very important element in an organization in achieving competitive advantage, so it is necessary to develop the quality of human resources with various efforts. The purpose of this study was to analyze and examine the effect of reward and punishment, and work culture on the performance of state civil servants through organizational commitment. The population in this study were civil servants with the category of civil servants in the Districts of Mangaran, Panji, and Situbondo. The sampling technique was determined by saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Reward and Punishment has a significant effect on organizational commitment, Reward and Punishment has a positive but not significant effect on performance, Work culture has a significant effect on organizational commitment, Work culture has a significant effect on performance, organizational commitment significant effect on performance. The results of the indirect effect hypothesis test show that the Reward and Punishment variable on Performance through Organizational Commitment has a significant effect, Work Culture on Performance through Organizational Commitment has a significant effect.